FORMATION OF A RANGE OF FUNCTIONAL FLOUR CONFECTIONERY PRODUCTS - Reznichenko I.Yu.; Renzyaeva T.V.; Tabatorovich A.N.; Surkov I.V.; Chistyakov A.M. (Техника и технология пищевых производств)
The article considers the problem of improving the range of confectionery from the standpoint of satisfaction of consumer demand in functional foods. The analysis of domestic and foreign scientific literature on promising directions of improving the range of functional confectionery is given. The article provides information on volumes of staple foodstuffs consumption in the Russian Federation taking into account the consumer basket. Identified is the diet imbalance as far as basic food substances, vitamins, micro- and macroelements are concerned. The structure of confectionery market in Russia and the Kemerovo region, as well as trends of its development is analyzed. The choice of the priority range for the development of functional flour confectionery products that meet modern requirements of healthy eating and Strategies for increasing the quality of food products in the Russian Federation until 2030 is substantiated. Doing their research the authors applied the methods of systematization, analysis and synthesis; sociological andstatistical ones. The research has been carried out on the base of the "Kemerovo technological Institute of food industry (University)". The new data compensating the lack of information about the dynamics and trends of the consumer market of flour confectionery products in Russia and abroad have been obtained. They also helped us to justify the need for innovative approaches to the increase of resource base, and the development of formulations and technologies of functional confectionery to improve their range. The findings have theoretical value and can be used by scientists and practitioners, whose activities are connected with the formation of the product range and the development of functional flour confectionery products.